Development and testing of a black pepper decorticator - GINU FRANCIS KARTHIAYANI A SREEJITH P. N; Dr. Santhi Mary Mathew (Guide) (Tavanur 2000 Kelappaji College of Agricultural Engineering and Technology)
the major parts were a cylinder with a rough inside surface, rotating shaft with vane arrangement
Development and testing of a black pepper decorticator